The Use of Finite Element Method in Analysing the Dynamic Characteristic of a Rotor System - Amir Zaki Mubarak (Jurnal Teknik Mesin Unsyiah, 2012)
Vibration analysis is very essential to be considered in designing a rotor system. The failure in rotor system parts can be avoided by understanding the dynamic characteristic. The objective of this research is to investigate the dynamic characteristic of rotor systems by using finite element method. Finite element method is used to reveal the system characteristic which is derived from the kinetic and potential energy equations. Some models of rotor systems are analysed to understand the dynamic characteristic. The natural frequencies are obtained from the eigen values. The simulation is carried out with the distance of disk from the support as the variable. The result shows that the distance between the disk and the bearing affects the natural frequency of the system.